2015
DOI: 10.1007/s00109-015-1268-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of folate and other one-carbon related nutrients with hypermethylation status and expression of RARB, BRCA1, and RASSF1A genes in breast cancer patients

Abstract: Hypermethylation at promoters of RARB, BRCA1, and RASSF1A is associated with reduced transcript levels of the respective gene in primary breast cancer tissue samples. Dietary folate and cobalamin intake is inversely associated with methylated RARB and BRCA1. High dietary intake of riboflavin and pyridoxine is associated with increased methylation in the RARB promoter. There is evidence for the age-dependent effects of nutrient intake on promoter methylation status. Bioavailability to the pool of nutrients migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 37 publications
0
34
2
Order By: Relevance
“…The T version of the MTHFR C677T polymorphism results in the substitution of an alanine residue with a valine, leading to a 50% reduction in enzymatic activity, and 10–20% of individuals in Western Europe and North America have the 677TT genotype . Observational studies have reported that higher levels of folic acid and vitamin B 12 in the diet are associated with higher global DNA methylation levels . However, contrary to our findings, Jung et al .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The T version of the MTHFR C677T polymorphism results in the substitution of an alanine residue with a valine, leading to a 50% reduction in enzymatic activity, and 10–20% of individuals in Western Europe and North America have the 677TT genotype . Observational studies have reported that higher levels of folic acid and vitamin B 12 in the diet are associated with higher global DNA methylation levels . However, contrary to our findings, Jung et al .…”
Section: Discussioncontrasting
confidence: 99%
“…Nutrients and other food components can modify DNA methylation patterns to modulate biological functions that influence health and aging. Higher intakes or status of several micronutrients participate in one‐carbon metabolism, including folate, choline, betaine, methionine, vitamin B 6 , and vitamin B 12 , which contribute to SAM production are associated with increased DNA methylation . Other nutrients, including flavanols and (–)‐epigallocatechin‐3‐gallate (EGCG), are competitive inhibitors of DNMTs through binding within the active site of the enzyme, leading to decreased global DNA methylation.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin C exhibits antioxidant actions including the neutralisation of free radicals, which may impact cancer progression 26,27 . Furthermore, dietary intake of folate was associated with a reduced death by inducing incorporation of uracil into DNA and inducing altered gene expression of critical tumor suppressor and proto-oncogenes via its role in DNA methylation 2830 . Epidemiological studies 31 and clinical trial 32 have suggested that a high fiber intake was related to reductions in blood levels of estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Only full-length original articles published in English were considered, and no attempt was made to include abstracts or unpublished data. This meta-analysis was planned, conducted, and reported according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statement 28 .…”
Section: Methodsmentioning
confidence: 99%
“…Due to the considerably increased incidence rate of breast cancer, it could be considered as one of the most common health problems across different populations [3,4]. In developing countries including Iran, patients diagnosed with breast cancer are 10 years younger compared to those in developed countries [3].…”
Section: Introductionmentioning
confidence: 99%